Social Media Police to Shape Citizen Ethics in The Digital Age - Syifa Nurul Latiefah; Widya Devita Sari; Deny Zein Tarsidi (Jurnal Civicus, 2022)
Along with the times, technological advances greatly affect all daily activities, one of which is the existence of social media which is a tool for communicating and socializing, there are many conveniences that are felt by the existence of social media, for example in the fields of education, economics, social and politics, but sometimes this communication in social media can backfire against the users themselves, this happens because of the unwise use of social media. The number of cases that are detrimental to victims in the unwise use of social media has become one of the triggers for conflicts and even divisions between groups, so that the government proposes to form social media police which is expected to be able to monitor social media users to be wiser in the use of social media and provide sanctions for anyone who violates this policy in the use of social media. With current technological advances, knowledge about how to be a good society is very much needed, so Digital Citizenship must begin to be formed for the whole community to shape the character of how to use social media well.